Smoking-Specific Experiential Avoidance is Indirectly Associated with Trait Worry and Smoking Processes among Treatment-Seeking Smokers - Farris, Samantha G. (Behav Med, 2014)
Limited work has examined worry, or apprehensive anticipation about future negative events, in terms of smoking. One potential explanatory factor is the tendency to respond inflexibly and with avoidance in the presence of smoking-related distress (smoking-specific experiential avoidance). Participants (n = 465) were treatment-seeking daily smokers. Cross-sectional (pre-treatment) self-report data were utilized to assess trait worry, smoking-specific experiential avoidance, and four smoking criterion variables: nicotine dependence, motivational aspects of quitting, perceived barriers to smoking cessation, and severity of problematic symptoms reported in past quit attempts. Trait worry was significantly associated with greater levels of nicotine dependence, motivation to quit smoking, perceived barriers for smoking cessation, more severe problems while quitting in the past; associations occurred indirectly through higher levels of smoking-specific experiential avoidance. Findings provide initial support for the potential role of smoking-specific experiential avoidance in explaining variable in the association between trait worry and a variety of smoking processes.